A new genus and two new species of Rhopalophorini Blanchard, 1845 (Coleoptera, Cerambycidae, Cerambycinae) - Martins, Ubirajara R.; Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2015)
A new genus and two new species of  Rhopalophorini Blanchard, 1845 are described, and figured: Allorhopaliella boliviana, gen. nov, sp. nov., from Bolivia; and Rhopalophora peruana sp. nov., from Peru. The new species of Rhopalophora Audinet-Serville, 1834 is included in a previous key.